Изотопно-геохимические различия нефтей аллохтонных и автохтонных комплексов Предкарпатья (в границах польско-украинского сегмента) - Лукин, А.Е.; Ладыженский, Г.Н.; Потера, Ю. (Видавничий дім "Академперіодика" НАН України, 2008)
The paper deals with the isotope-geochemical indices between the oils of different fields of the Carpathian Foredeep on the territory of Poland and Ukraine. Substantial distinctions by the indices δ¹³C, δD, and δ^34S are established between the oils of autochthonous and allochthonous complexes. In the light of isotopic criteria, the conclusion about a powerful practically non-realized hydrocarbon potential of the Ukrainian Carpathian autochthone is made.